PERANAN KURATOR DALAM PERMASALAHAN KEPAILITAN PERSEROAN TERBATA (STUDI KASUS PT NY.MENEER) - Kusumadewi, Dimitria Pawestri (Jurnal Hukum Statuta, 2024)
Bankruptcy is a situation where a company is declared unable to pay its debts and the impact can spread to various components of the economy, both local and global. Bankruptcy institutions are very important in maintaining market stability and order and protecting the interests of creditors and debtors. Law Number 34 of 2007 concerning Bankruptcy and Postponement of Debt Payment Obligations (PKPU) is a legal product that aims to ensure fair law enforcement and support national economic growth. In this research, the main focus is the role and obstacles faced by curators in handling PT bankruptcy. Mrs Meneer. PT case. Mrs. Meneer, who was declared bankrupt with total debts of 89 billion to 35 creditors, illustrates the importance of the curator's role in the bankruptcy process. The curator is responsible for managing and settling the bankruptcy estate for the benefit of all parties involved.